The Brake Public Debt Rule as An Instrument to Stabilize the Debt – Results for Poland - Przybylska-Mazur, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The public debt brake rule is the numerical fiscal rule applied the first time in Switzerland. In this paper we use the expenditure rule that is the core of the brake public debt rule for analyses the general government deficit and the government debt in Poland. When we use the brake public debt rule we assume that government spending does not result from a predetermined path, but they are linked to the level of revenue and variable economic situation. Unlike the original version of the brake public rule, in the paper we include the total expenditure and the total revenues being the sum of tax and non-tax revenues assumed in the Budget Laws. The potential GDP was determined on the basis of the HP filter. In addition my contribution to the topic is to investigate whether the implementation of the public debt brake rule in Poland will stabilize the general government deficit and the government debt over the business cycle and will reduce the ratio of debt to GDP
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 365-372
Keywords: brake public debt rule; expenditure rule; balanced budget; business cycle